2005
DOI: 10.1590/s0102-37722005000300012
|View full text |Cite
|
Sign up to set email alerts
|

Gender divergence in physical education classes

Abstract: -We evaluate a group of students, presumed by their physical education teachers to be gender divergent. This study suggests that PE teachers confuse "gender-divergence" with uncoordinated motor behaviors. This may be because PE classes emphasize motor abilities and coordination and PE teachers may pay particular attention to these characteristics and use them (wrongly) as a criterion for gender divergence. However, the 10 presumed "divergent students" differ from their peers by being more likely to have friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
2
3
0
5
Order By: Relevance
“…Similar results were found in other studies, such as that by Cardoso et al (2005), which compared gender ''atypical'' boys (as identified by their physical education instructors) with other classmates and noticed significant differences in their choices for soccer and other sports. In another study of the sexual orientation of fishermen on the south coast of Brazil, Cardoso (1994Cardoso ( , 2002Cardoso ( , 2005a obtained similar results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were found in other studies, such as that by Cardoso et al (2005), which compared gender ''atypical'' boys (as identified by their physical education instructors) with other classmates and noticed significant differences in their choices for soccer and other sports. In another study of the sexual orientation of fishermen on the south coast of Brazil, Cardoso (1994Cardoso ( , 2002Cardoso ( , 2005a obtained similar results.…”
Section: Discussionsupporting
confidence: 89%
“…There is an interactive effect among the three categories (p < .003; partial g 2 = .018) fewer homosexuals bullied others or liked to fight in their childhood (see Ellis, Hoffman, & Burke, 1990;Werner, 1998Werner, , 2006. These results, coupled with previous cross-cultural research (Bartlett & Vasey, 2006;Cardoso, 2005;Whitam, 1983;Whitam & Mathy, 1986), suggest that cross-gender behavior and identity in childhood is a universal pattern of The main and the simple effects of the ANCOVA 3 (sexual orientation) 92 (social class l) 93 (nationality), controlling for age and consumer items are described as follows: * Significant differences were verified among the sexual orientations (p < .001; partial g 2 = .254) and in the participants' nationalities (p < .001; partial g 2 = .035) in the childhood desire to be a girl. Interactive effects were verified between sexual orientation and social class (p < .001; partial g 2 = .046) and between nationality and sexual orientation (p < .001; partial g 2 = .048) ** Significant differences were verified among the sexual orientations (p < .001; partial g 2 = .217) and social classes (p < .01; partial g 2 = .008) in childhood cross-dressing.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It is important to highlight that these results come from a European culture where access to physical activities and physical education may be more evenly divided, although not necessarily evenly encouraged, compared with Brazil. In Brazil, we argue that there is both more limited access as well as less cultural encouragement for girls to engage in gross motor physical activities (Cardoso et al 2005). A recent study found poorer performance of girls from 3 to 10 years old, in locomotor and object control skills, as a consequence of limited opportunities for motor development in school settings (Spessato et al 2013).…”
Section: Age and Gender Mediate The Lack Of Motor Experiencementioning
confidence: 86%
“…Hoje, graças a alguns bravos pesquisadores preocupados com a transdisciplinaridade do conhecimento cientifico, sabemos que em muitas sociedades a maioria dos homens homossexuais teve uma infância atípica em termos de gênero e outras habilidades e preferências Cardoso, 2002;Cardoso, Felipe & Hedegaard, 2003;Davenport, 1986;Green, 1987;Grellert, Newcomb & Bentler, 1982;Hockenberry & Billingham, 1987;Whitam, 1983;Zucker, 1990;), mas somente uma minoria desses homossexuais desenvolve uma atração por travestir-se. Por outro lado, nos Estados Unidos e em países do norte europeu, existe um número considerável de travestis ou de transexuais bissexuais e heterossexuais que, a princípio, tiveram uma infância típica.…”
Section: Considerações Finaisunclassified